SC10 Regional emergency department simulation: where are we starting from?. (17th November 2016) - Pritchett, CSA; Slade, T; Langford, R
Abstract : Background: The National Simulation Development Project Summary Report 1 is a beneficial report benchmarking current simulation provision and outlining future direction in the UK. A key theme is the significance of regional networks. In this service evaluation, we establish current regional resource and usage within Emergency Department (ED) simulation across the Health Education Southwest (HESW) region. Methodology: Questionnaires were issued to all EDs in the HESW region. Responses were collected over a 2 month period. These sought to establish: Location and frequency of simulation training Participants undertaking, designing and delivering simulation Use of standardised scenario templates Simulation equipment, faculty training and time available Use of simulation in local governance Barriers to simulation Results: 8 of 11 departments responded (73%). 87.5% used in-situ simulation and 100% used simulation- suite based scenarios. All departments run multidisciplinary simulations with 75% including anaesthetic, orthopaedic and general surgery doctors. 62.5% designed scenarios around a standardised proforma. Scenario development involved ED consultants (100%), middle grades/registrars (87.5%) or anaesthetists (62.5%). All departments had formally trained faculty, frequently by 'train the trainer' courses. 25% of faculty had funded SPA time for simulation training. Most departments (87.5%) had access to 'sim man 3G', dedicated equipment and a resus bay (87.5%). Dedicated technician support was available in 75% of departments. Simulation scenarios were developed around recent ED cases (87.5%) or local serious incidents (75%). 37.5% used simulation as a tool to measure change as part of QI or audit cycle. Cited barriers to development were lack of consultant time and operational pressures. Conclusions and recommendations: Simulation has been embraced by EDs within HESW. All departments receive locally delivered simulation by appropriately trained staff. Future development will include: Curriculum mapping to maximise learning opportunities for trainees. Use of simulation within local governance.